SISTEM INFORMASI GEOGRAFIS PEMETAAN DAERAH RAWAN BEGAL BERBASIS WEB DI KOTA PEKANBARU - Yuda Irawan (RJOCS (Riau Journal of Computer Science), 2019)
Pekanbaru City Police Department said that the level of crime in security and public order increased in 2017 compared to the previous year. In 2016 there were 1,847 cases, up to 2,043 cases in 2017. Far enough, around 196 cases, or 9.59 percent, were data recorded by the police of Pekanbaru resorts. The most prominent cases were theft with weights (Curat), which were 381 cases. The second is cases of narcotics and illegal drugs with 234 cases. Whereas the third rank is the case of motor vehicle theft (Curanmor) and the hijacking which is currently rife again in the city of Pekanbaru because almost every day there is news about cases of halt that occurred in the City of Pelanbaru. Geographic Information Systems (GIS) can be presented in the form of desktop applications or web-based applications that can provide an explanation of an event, make forecasting events, and other strategic planning by mapping the position of objects on the surface of the earth. It is very much needed by Pekanbaru people and immigrants to get information and find out about the location of vulnerable criminal areas in the city of Pekanbaru